54 Application of multidisciplinary in-situ simulation and process improvement techniques to improve the quality, efficiency and effectiveness of category one caesarean sections. (17th November 2016) - Jayaweera, SR; Michell, VA; Jackson, G; Rosenorn-Lanng, D
Abstract : Background: A category one caesarean section is an obstetric emergency due to an immediate threat to the life of the mother or baby with a gold standard 30 minute decision to delivery interval (DDI). 1 This requires a complex series of activities involving large multi-disciplinary teams working under time-pressured conditions. Our approach combined in-situ simulation and Six Sigma methodology as quality improvement tools to refine this complex clinical process and reduce clinical risk. Methodology: Methodology was based on DMAIC (Define, Measure, Analyse, Improve and Control) cycles. Four multi-disciplinary in-situ simulations were conducted using a standardised scenario to produce a baseline process map. Qualitative data were collected after each simulation. The data was analysed using Six Sigma methodology; an evidence based, data driven quality improvement and problem-solving approach pioneered by the manufacturing industry. Ishikawa charts were used to identify issues related to efficiency and clinical risk. Interventions were designed and embedded with six subsequent simulations. Further qualitative data were collected to assess the improvement resulting from the new process. Results: Issues were categorised into 4 areas: communication between staff, handover of information, roles and responsibilities, and the WHO checklist. The primary intervention was an emergency bleep for category one caesarean sections. Secondary interventions were the introduction of key handover points and promoting awareness of the WHO checklist. Qualitative data demonstrated improvements in communication and role clarity. A retrospective notes analysis is scheduled for July 2016 to analyse DDI before and after the interventions. Conclusions and recommendations: We recommend combining in-situ simulation and Six Sigma methodology to identify issues and develop improvements in complex, multi-disciplinary clinical processes. This enables multiple focused interventions to reduce clinical risk and improve clinical efficiency. Reference: Classification of Urgency of Caesarean Section – a Continuum of Risk (Good Practice No. 11) [Internet]. 2010 [cited 22/01/2016]. Available from: https://www.rcog.org.uk/globalassets/documents/guidelines/goodpractice11classificationofurgency.pdf